The Trusting Beliefs of Users and the Intention to Continue Making Purchases via Social Commerce - Ghina Fitri Ariesta Susilo; Utpala Rani; Siti Afidatul Khotijah (Faculty of Economics and Business, Universitas Gadjah Mada, 2022)
Introduction/Main Objectives: This study aims to examine the influence of a user’s trusting beliefs on the intention to continue making purchases via social commerce. Indonesia is ranked 4th in the world for the most active online users of social media. Thus, it is necessary to investigate the influence of those variables. Background Problems: Social networks contribute to online trading by providing platforms for social commerce. The author chose the trusting beliefs concept and linked it to online users’ trust in social commerce. Novelty: Trusting beliefs variables are fundamental in shaping online users’ behaviors, but no prior research has investigated the effect of trusting beliefs on the intention to make purchases via social commerce. This study presents new research that provides a comprehensive model related to social commerce. Research Methods: This research uses purposive sampling of people who are required to have social media accounts and who have made purchases via social commerce at least once with data taken from surveys. The research uses Structural Equation Modelling (SEM). Finding/Results: This study proves that all trusting beliefs variables are supported and significant, but there is one hypothesis that is not supported (H4). Empirically, this indicates that active users are not necessarily engaging in online shopping using their social media. Conclusion: This study provides insights into the potential role of trusting beliefs driving continuing purchases in the context of social commerce research. We suggest that the sellers need to give customers-to-be more frequent and wider product reviews information so they can get results in terms of stronger product image and motivate them to make purchases via social commerce.